DAMPAK DIGITAL MARKETING, INTERAKSI MEDIA SOSIAL, E-SERVICE QUALITY, DAN DISKON TERHADAP KEPUASAN PELANGGAN PADA DAILYTOP SHOP DI KOTA PALOPO - Jamal, Fitriani; Maszudi, Edi; Riyanti, Riyanti (PRIMA EKONOMIKA, 2026)
ABSTRACT The development of information and communication technology has drastically changed consumers starting from searching for information, communication media, to shopping done with the help of social media which has a very large contribution for Dailytop Shop Fashion sellers in Palopo City which has an impact on consumer purchasing interest. The purpose of this study is to determine how the influence of digital marketing, social media interaction, e- service quality, and promotional discounts on customer satisfaction. The method used in this study is quantitative with a sample of 222 respondents with. Data collection techniques by distributing respondents (purposive sampling). Data analysis techniques use instrument analysis tests, classical assumption tests, multiple linear regression tests, hypothesis tests using SPSS 26 software. Based on the results of the study, digital marketing, social media interaction, E-service quality, promotional discounts on customer satisfaction is 73.7% and the remaining 26.3% is influenced by other variables outside this regression equation or other variables not examined in this study. Keywords: Digital Marketing; Social Media; E-service quality; Promotional discounts; Customer satisfaction